ʿIlm al-ʿumrān and the contemporary discourse on Islamisation of knowledge: A critical reappraisal - Wan Zakaria, Wan Fariza Alyati; Yaakob, Zul'azmi; Salleh, Nozira; Dewi, Ernita; Taufik, A (Journal of Islamic, Social, Economics and Development, 2026)
This article examines the prevailing reliance on Western paradigms in the social sciences within Muslim societies. It proposes an alternative approach rooted in Islamic intellectual tradition, particularly through the framework of ʿilm al-ʿumrān, as articulated by Ibn Khaldūn. The paper explores the definition, objectives, and characteristics of Islamic social science, critiquing the compartmentalization of knowledge in Western traditions. Drawing from Merryl Wyn Davies’ work, the article argues for a civilisational and integrated model of social science that aligns with the metaphysical and moral worldview of Islam.